The immunological synapse as a pharmacological target. (August 2018) - Finetti, Francesca; Baldari, Cosima T.
Graphical abstract: Abstract: The development of T cell mediated immunity relies on the assembly of a highly specialized interface between T cell and antigen presenting cell (APC), known as the immunological synapse (IS). IS assembly is triggered when the T cell receptor (TCR) binds to specific peptide antigen presented in association to the major histocompatibility complex (MHC) by the APC, and is followed by the spatiotemporal dynamic redistribution of TCR, integrins, co-stimulatory receptors and signaling molecules, allowing for the fine-tuning and integration of the signals that lead to T cell activation. The knowledge acquired to date about the mechanisms of IS assembly underscores this structure as a robust pharmacological target. The activity of molecules involved in IS assembly and function can be targeted by specific compounds to modulate the immune response in a number of disorders, including cancers and autoimmune diseases, or in transplanted patients. Here, we will review the state-of-the art of the current therapies which exploit the IS to modulate the immune response.